2015
DOI: 10.1098/rstb.2013.0385
|View full text |Cite
|
Sign up to set email alerts
|

The ancient Yakuts: a population genetic enigma

Abstract: This study is part of an ongoing project aiming at determining the ethnogenesis of an eastern Siberian ethnic group, the Yakuts, on the basis of archaeological excavations carried out over a period of 10 years in three regions of Yakutia: Central Yakutia, the Vilyuy River basin and the Verkhoyansk area. In this study, genetic analyses were carried out on skeletal remains from 130 individuals of unknown ancestry dated mainly from the fifteenth to the nineteenth century AD. Kinship studies were conducted using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…The most commonly accepted hypothesis proposes that they descend from a founding population brought by the Yakut people (2,4). Some authors have suggested that at the time of their arrival, founding horses admixed with local populations descending from wild Late Pleistocene horses (8)(9)(10).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly accepted hypothesis proposes that they descend from a founding population brought by the Yakut people (2,4). Some authors have suggested that at the time of their arrival, founding horses admixed with local populations descending from wild Late Pleistocene horses (8)(9)(10).…”
Section: Significancementioning
confidence: 99%
“…Despite such extreme conditions, a group of Turkic-speaking horse-riders, likely originating from the AltaiSayan and/or Baïkal area, migrated into this region between the 13th and 15th centuries, pressed by the expansion of Mongolic tribes (2)(3)(4). The Yakut people successfully developed a unique economy based on horse and cattle breeding, with Yakutian horses mostly exploited as sources of meat and milk.…”
mentioning
confidence: 99%
“…It was shown by studies of Y-chromosomal short tandem repeats (Y-chromosomal STR) that the Yakuts are characterized by low genetic diversity in Y-chromosomal loci. This fact is considered to be caused by strong reduction in a male population size of Yakuts and existence population bottleneck during their migration in the historical past [47,54,55]. In this scenario it is possible that the Yakut population is characterized by increased incidence any genetic variants associated with impaired spermoigenesis due to founder effect.…”
Section: Discussionmentioning
confidence: 99%
“…Green cryo-fodder is the basis of nutrition for many animals, including the Yakutian horses. This breed is considered a direct successor and descendant of the horses brought from the Baikal region in the 13th-15th centuries AD [9][10][11]. The origin of the horses was confirmed by molecular genetic methods [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%